ANALISIS KELAYAKAN USAHA JASA FITNESS CENTER DI KOTA PEKANBARU - Jenni Meri; Setiawan Deny; Maulida Yusni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the feasibility of a fitness center (GYM) service business in Pekanbaru City in terms of non-financial aspects, namely marketing and socio-economic aspects and financial aspects. This research was conducted in Pekanbaru City and the object of research is a fitness center (GYM) service business in Pekanbaru City. The data were analyzed by descriptive analysis to see the feasibility of a fitness center (GYM) service business in terms of marketing, from a socio-economic point of view and quantitative data analysis to see the feasibility of a fitness center (GYM) service business from a financial point of view, using the analysis of Net Present Value ( NPV), Benefit Cost Ratio (B/C Ratio), Internal Rate of Return (IRR). The results of research conducted from 13 respondents indicated that the feasibility of the marketing aspect of the fitness center (GYM) service business was feasible. From the socio-economic aspect, the fitness center (GYM) service business is feasible to run. The fitness center (GYM) service business from the financial aspect produces a Net Present Value of Rp. 333,707,315>0, then the fitness center (GYM) service business is feasible to run. The B/C Ratio value is 1.84>1, then the fitness center (GYM) service business is feasible to run. The IRR value is 22.80%>12%, then the fitness center (GYM) service business is feasible to run.Keywords: Financial Analysis, Non-Financial Analysis, Fitness Center (GYM)